Pemberdayaan Lansia Melalui UPTD Panti Sosial Rehabilitasi Lansia Jawa Barat - Anggita Ghaidhasani Marudi; Deden Sumpena; Dedi Herdiana (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
Increased AHH accompanied by an increase in the elderly population. It is feared to bring impact on socio-economic conditions of the country. The phenomenon must look for a solution, the one with the empowerment program for seniors. UNIT for The Social Rehabilitation and Elderly West Java is one of the Government agencies that become facilitators in the empowerment of the elderly. The goal in this research to know the process of empowerment and continuity in the program of empowerment. Peneltian is done based on the qualitative method through a descriptive approach. The theory in this research is the theory of Hogan that saw that the process of empowerment is a process that goes on all human life derived from individual experience, instead of a process that stops at a time only. The results in this study is granting the empowerment program in the form of skills training where in the process conducted during twice a week and training conducted by a competent instructor, it is aimed so that the creation of the elderly independent work, and quality.